Revision of the genus Ptilothyris Walsingham, 1897 (Lepidoptera: Gelechioidea: Lecithoceridae), with descriptions of eight new species from Africa - Park, Kyu-Tek; Mey, Wolfram; Koo, Jun-Mo; de Prins, Jurate; Cho, Soowon (Zootaxa, 2019)
Ptilothyris Walsingham, 1897, a poorly known Afrotropical genus of Lecithoceridae, is revised. Eight new species are described and illustrated: P. subcucullata Park, sp. nov., P. crassiella Park, sp. nov., P. drepanodes Park, sp. nov., P. enormisella Park, sp. nov., P. hylodes Park, sp. nov., P. leifaarviki Park, sp. nov., P. pilosa Park, sp. nov., and P. vokaensis Park, sp. nov. Each species is compared with type specimens of the related species deposited in various museums worldwide. COI barcode sequences of six species were successfully obtained and are provided. Of the 13 previously known African species of the genus, P. serangota ab. cyanea Ghesquière, 1940 is synonymized with P. serangota Meyrick, 1932, and the following three species are excluded from the genus: brachysema Meyrick, 1938, crocophracta Meyrick, 1938, and nemophorella Ghesquière, 1940. The latter three will be transferred to related genera in forthcoming studies. Adults and genitalia of all the known species including the new species are illustrated, and a key to the species is provided.